2014
DOI: 10.1186/s12985-014-0230-z
|View full text |Cite
|
Sign up to set email alerts
|

IL-22-producing Th22 cells play a protective role in CVB3-induced chronic myocarditis and dilated cardiomyopathy by inhibiting myocardial fibrosis

Abstract: BackgroundA new subset of T helper (Th) cells, named IL-22-producing Th22 cells, was identified recently. Th22 cells have been implicated in immunity and inflammation. However, the role of these cells in the progression from acute viral myocarditis (AVMC) to dilated cardiomyopathy (DCM) and myocardial fibrosis remains unknown.MethodsBALB/c mice were repeatedly i.p. infected with Coxsackie virus B3 (CVB3) to establish models of AVMC, chronic myocarditis and DCM. On week 2, 12 and 24 post initial injection, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 31 publications
1
34
0
Order By: Relevance
“…Tissues were subjected to sectioning (5 μm thickness) as well as hematoxylin and eosin (H&E) stain. Cardiac fibrosis was analyzed by staining RV tissue sections with Masson’s trichrome stain, and collagen volume fraction (CVF) was assessed as previously described [35]. Cardiomyocyte cross-sectional area was assessed by staining RV tissues with wheat germ agglutinin conjugated to Alexa Fluor® 488 dye (WGA, Invitrogen, Carlsbad, CA, USA) and counterstained for nuclei with 4, 6-diamidino-2-phenylindole (DAPI, Sigma-Aldrich, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Tissues were subjected to sectioning (5 μm thickness) as well as hematoxylin and eosin (H&E) stain. Cardiac fibrosis was analyzed by staining RV tissue sections with Masson’s trichrome stain, and collagen volume fraction (CVF) was assessed as previously described [35]. Cardiomyocyte cross-sectional area was assessed by staining RV tissues with wheat germ agglutinin conjugated to Alexa Fluor® 488 dye (WGA, Invitrogen, Carlsbad, CA, USA) and counterstained for nuclei with 4, 6-diamidino-2-phenylindole (DAPI, Sigma-Aldrich, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…However, our knowledge is limited, and elevated level of IL-22 was demonstrated in the heart of mice with dilated cardiomyopathy and cardiac fibrosis. Treatment of mice with IL-22-specific antibody decreased the survival rate of the animals and exacerbated myocardial fibrosis suggesting the cardioprotective role of IL-22 through the inhibition of myocardial fibrosis [ 84 ].…”
Section: Role Of Il-10 Family Members In Fibrotic Diseasesmentioning
confidence: 99%
“…In addition, percentage of Th22 cells (CD4 + IFN‐γ − IL‐17 − IL‐22 + cells) was notably increased in acute myocardial infarction (2.23 ± 1.58%) and unstable angina (2.09 ± 0.60%) patients compared with stable angina patients (0.93 ± 0.26%) or healthy controls (0.84 ± 0.18%) . In contrast, the results of dilated cardiomyopathy (DCM) studies showed that Th22 cells may inhibit myocardial fibrosis, indicating that these cells may have a protective role in DCM . Thus, the role of Th22 cells in cardiovascular disease (CVD) needs to be further explored.…”
Section: Discussionmentioning
confidence: 99%